Studi Kelayakan Kawasan Kampung Wisata Yang Berada di Desa Leuwiliang - salsa rahmatina; Said Bambang Nurcahya (Jurnal Perhotelan dan Pariwisata, 2026)
The tourisme village (kampung wisata) in the cicalengka area represents a from of destination development that integrates local natural resources, cultural herigate, and community creativity. This study is to describe the characteristics, potentials, and roles of the tourisem village in cicalengka as an alternative attraction capable of improving the local economy. A qualitative descriptive approach was used through direct observation and information gathering from managers, community members, and visitors. The findings show that the Tourism Village in Cicalengka has strong advantagesin its authentic environment, cultural attractions, and educational activities such as agriculture, local arts, and traditional culinary experiences. Community-based management contributes to sustainability and provides direct economic benefits to local residents. However, several challenges remain, including limited infrastructure, insufficient digital promotion, and the need to improve management capacity. Overall, the Tourism Village in Cicalengka has the potential to become a leading destination if supported by proper governnacem facility development and collaboration between village authorities, small business, and the community. This potential offers significant opportunities to enchance residents quality of life and strengthen Cicalengkas identity as an attractive and competitive tourism. Keywords : Tourism Village, Cicalengka Community-based tourism. Destination development, local economy, village potential, education toursm, sustanibility.